An unusual case of paravaginal sebaceous cyst posing diagnostic dilemma (Indian Journal of Case Reports, 2024)
The prevalence of vaginal cysts is uncertain since many go unreported but it is estimated that 1 out of 200 women have a vaginal cyst. We report a case of a 23-year-old female with secondary infertility with an incidental asymptomatic vaginal cyst, which was originally misdiagnosed as an endometriotic cyst. We performed the surgical treatment with negative hysterolaparoscopic findings, only to identify a paravaginal sebaceous cyst on vaginal exploration. Pathology results confirmed that the cyst wall was lined by stratified squamous keratinizing epithelium with a lumen containing lamellated keratin. The features were suggestive of epithelial inclusion cyst.